1971
DOI: 10.1346/ccmn.1971.0190405
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Pore Structure of Impact-Compacted Clays

Abstract: Abstract-The microstructures of impact-compacted kaolinite and illite clays, after drying, were investigated by pore size-distribution measurements, X-ray orientation determinations, and scanning electron microscopy. Clays compacted on the dry side of the optimum moisture content exhibited a domain structure with adjacent domains largely separated by micrometer-size interdomain voids; clays compacted at or above the optimum moisture content showed a more nearly massive structure, large interdomain voids being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
45
0
3

Year Published

1974
1974
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 10 publications
5
45
0
3
Order By: Relevance
“…Although the microstructure of soils compacted dry of optimum (including a kaolinite) had been described by Diamond (1970) as 'a domain structure with adjacent domains largely separated by micrometer-sized interdomain voids' (domain being another term for aggregate), Sridharan et al did not refer to any aggregate microstructure in their interpretation of the nature of the pores. The results of Sridharan et al can be redrawn as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although the microstructure of soils compacted dry of optimum (including a kaolinite) had been described by Diamond (1970) as 'a domain structure with adjacent domains largely separated by micrometer-sized interdomain voids' (domain being another term for aggregate), Sridharan et al did not refer to any aggregate microstructure in their interpretation of the nature of the pores. The results of Sridharan et al can be redrawn as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The pore size distribution was determined from the pressure and intrusion data using Equation (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) …”
Section: -41 Data Reductionmentioning
confidence: 99%
“…Predictive equations already created for frost heave rate in such soils require no modifications . 17. Key Words soil fabric; pore size distribution; air permeability, water permeability; frost heave rate; soil-moisture characteristic curve; equilibrium water content; mineralogic effects 18.…”
mentioning
confidence: 99%
“…Hence Equation (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) can be rewritten as: The term G(x.) defined in Equation (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) (4)(5)(6)(7)(8)(9)(10)(11)(12) . A subroutine called "CADRE" in the Purdue University CDC 6500-6600 computer library was utilized to carry out this numerical integration.…”
mentioning
confidence: 99%